GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 296 species occurrences available in GBIF matching the query: TaxonKey: Lilium pensylvanicum Ker Gawl.. The dataset includes 296 records from 33 constituent datasets: 4 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 14 records from Naturalis Biodiversity Center (NL) - Botany. 1 records from University of Alberta Vascular Plant Herbarium (ALTA). 1 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 1 records from Australia's Virtual Herbarium. 1 records from UCBG TAPIR Provider. 1 records from NMNH occurrence DwC-A. 1 records from OAC-BIO Herbarium. 1 records from Vascular plant specimens of Akita Prefectural Museum. 1 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 7 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 1 records from Tropicos Specimen Data. 1 records from Natural History Museum (London) Collection Specimens. 154 records from Ibaraki Nature Museum, Vascular Plants collection. 1 records from Australian National Herbarium (CANB). 4 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 1 records from Botanic Garden of the Finnish Museum of Natural History. 2 records from Plant in Baekdu Mountain (KIDR-PL). 1 records from DAO Herbarium Type Specimens. 1 records from Herbarium Berolinense. 1 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 6 records from United States National Plant Germplasm System Collection. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 1 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 3 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 32 records from Plant. 41 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Bernice P. Bishop Museum. 2 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from Botany (UPS). 2 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1 records from Green Plant Herbarium (TRT). 5 records from SysTax - Botanical Gardens.
Keywords: GBIF; biodiversity; species occurrences